Sustained mitochondrial biogenesis is essential to maintain caloric restriction-induced beige adipocytes - Mooli, Raja Gopal Reddy (Metabolism, 2020)
BACKGROUND: Caloric restriction (CR) delays the onset of metabolic and age-related disorders. Recent studies have demonstrated that formation of beige adipocytes induced by CR is strongly associated with extracellular remodeling in adipose tissue, decrease in adipose tissue inflammation, and improved systemic metabolic homeostasis. However, beige adipocytes rapidly transition to white upon CR withdrawal through unclear mechanisms. MATERIALS AND METHODS: Six-week old C57BL6 mice were fed with 40% CR chow diet for 6 weeks. Subsequently, one group of mice was switched back to ad libitum chow diet, which was continued for additional 2 weeks. Adipose tissues were assessed histologically and biochemically for beige adipocytes. RESULTS: Beige adipocytes induced by CR rapidly transition to white adipocytes when CR is withdrawn independent of parkin-mediated mitophagy. We demonstrate that the involution of mitochondria during CR withdrawal is strongly linked with a decrease in mitochondrial biogenesis. We further demonstrate that beige-to-white fat transition upon β3-AR agonist-withdrawal could be attenuated by CR, partly via maintenance of mitochondrial biogenesis. CONCLUSION: In the model of CR, our study highlights the dominant role of mitochondrial biogenesis in the maintenance of beige adipocytes. We propose that loss of beige adipocytes upon β3-AR agonist withdrawal could be attenuated by CR.